Eugene O‟neill‟s Duality of Structure Reflected on All God’s Chillun Got Wings - Nufiarni, RIzki (Universitas Negeri Semarang, 2018)
In Gidden‘s Structuration theory, the most important concept is duality of structure, where agent and structure affects each other and have equally important position. This article is written to find out the duality of structure in Eugene O‘Neill drama entitled All God‘s Chillun Got Wings. The analysis is trying to examine the drama as one of O‘Neill‘s power to change the structure that he has. The analysis unit for the structure is taken from the the literature about the social background in American society in the late 19 th century and early 20 th century, while the analysis unit for the agent is taken from O‘Neill‘s drama as a reflection of the action in which O‘Neill implemented his power. Therefore, it is concluded that O‘Neill duality of structure can be observed through his action in the drama to change the structure which shaped him as an agent. Some of his actions has resulted in an unintended consequences which will become an unacknowledged condition of actions for another action.